James Ivory in conversation : how Merchant Ivory makes its movies - Ivory, James (University of California Press, 2005)
"James Ivory in Conversation is an exclusive series of interviews with a director known for the international scope of his filmmaking on several continents. Three-time Academy Award nominee for best director, responsible for such film classics as A Room with a View and The Remains of the Day, Ivory speaks with remarkable candor and wit about his more than forty years as an independent filmmaker. In this deeply engaging book, he comments on the many aspects of his world-traveling career: his growing up in Oregon (he is not an Englishman, as most Europeans and many Americans think), his early involvement with documentary films that first brought attention to him, his discovery of India, his friendships with celebrated figures here and abroad, his skirmishes with the Picasso family and Thomas Jefferson scholars, his usually candid yet at times explosive relations with actors. Supported by seventy illuminating photographs selected by Ivory himself, the book offers a wealth of previously unavailable information about the director's life and the art of making movies. James Ivory on:On the Merchant Ivory Jhabvala partnership:"I've always said that Merchant Ivory is a bit like the U.S. Government; I'm the President, Ismail is the Congress, and Ruth is the Supreme Court. Though Ismail and I disagree sometimes, Ruth acts as a referee, or she and I may gang up on him, or vice versa. The main thing is, no one ever truly interferes in the area of work of the other."On Shooting Mr. and Mrs. Bridge:"Who told you we had long 18 hour days? We had a regular schedule, not at all rushed, worked regular hours and had regular two-day weekends, during which the crew shopped in the excellent malls of Kansas City, Paul Newman raced cars somewhere, unknown to us and the insurance company, and I lay on a couch reading The Remains of the Day."On Jessica Tandy as Miss Birdseye in The Bostonians:"Jessica Tandy was seventy-two or something, and she felt she had to 'play' being an old woman, to 'act' an old woman. Unfortunately, I'couldn't say to her, 'You don't have to 'act' this, just 'be, ' that will be sufficient.' You can't tell the former Blanche Du Bois that she's an old woman now."On Adapting E.M. Forster's novels"His was a very pleasing voice, and it was easy to follow. Why turn his books into films unless you want to do that? But I suppose my voice was there, too; it was a kind of duet, you could say, and he provided the melody."On India:"If you see my Indian movies then you get some idea of what it was that attracted me about India and Indians ... any explanation would sound lamer than the thing warrants. The mood was so great and overwhelming that any explanation of it would seem physically thin ... I put all my feeling about India into several Indian films, and if you know those films and like them, you see from these films what it was that attracted me to India."On whether he was influenced by Renoir in filming A Room with a View "I was certainly not influenced by Renoir in that film. But if you put some good looking women in long white dresses in a field dotted with red poppies, andthey're holding parasols, then people will say, 'Renoir.'"On the Critics:"I came to believe that to have a powerful enemy like Pauline Kael only made me stronger. You know, like a kind of voodoo. I wonder if it worked that way in those days for any of her other victims-Woody Allen, for instance, or Stanley Kubrick."On Andy Warhol as a dinner guest:"I met him many times over the last twenty years of his life, but I can't say I knew him, which is what most people say, even those who were his intimates. Once he came to dinner with a group of his Factory friends at my apartment. I remember that he or someone else left a dirty plate, with chicken bones and knife and fork, in my bathroom wash basin. It seemed to be a symbolic gesture, to be a matter of style, and not just bad manners."--